PROSEDUR REVIEW ATAS LAPORAN KEUANGAN AUDITAN DI KAP KKSP YOGYAKARTA - Nova Kusumaningrum; Yulida Army Nurcahya (Universitas Prof.Hazairin,SH Bengkulu, 2020)
This audited financial statement is one of the most important aspects for an auditor. This is important because an auditor is required to be able to present quality audited financial statements for clients. The objectives of this study are (1) to find out the history of KAP KKSP Yogyakarta; (2) to find out auditors in KAP KKSP Yogyakarta in presenting audited financial statements; and (3) to find out how to review audited financial report procedures at KAP KKSP Yogyakarta. The method used in this research is to use a descriptive method which is a research method to make a picture of a situation or event so that this method does not only hold simulations of the data available in the field. The results of this study are that conducting an audited financial statement review is very important to be carried out by an auditor because it can present a qualified audited financial report so as to maintain the engagement between the client and KAP KKSP Yogyakarta.